THE RELATIONSHIP BETWEEN SOUNDSCAPE AND CHINESE CULTURE – A CASE STUDY OF THE WEST LAKE SCENIC AREA - J. Ge; M. Guo; Y. H. Zhu; J. Jia; Y. Zhang (International Association of Lowland Technology, 2012)
Soundscape is a new interdisciplinary field of landscape and acoustics. This paper is intended to study the relationship between soundscape and culture. That is, the Chinese culture’s pursuit of acoustic beauty from three aspects as poetries, writings and drawings. It is demonstrated by the case study of soundscape in West Lake scenic area, with particular emphasis on humane attribute. The study has approached by three steps as classification - case study - promotion to region. The major attractions of West Lake scenic area is divided into natural and artificial categories, and the typical cases selected are “Orioles Singing in the Willows” and “Evening Bell Ringing at Nanping hill.” The two cases are analyzed from two aspects as the cultural background and humanities artistic conception, in order to prove the subject. And the importance of soundscape culture research to the construction of West Lake scenic area is declared further.